SOCIAL AVOIDANCE IN MODERN SOCIETY IN SAD GIRLS BY LANG LEAV - Ni Gusti Ayu Intarini, Ni Gusti Ayu Intarini; Thohiriyah, Thohiriyah (ELTIN Journal, 2024)
This study discusses the phenomenon of social avoidance in modern society as depicted in the novel ‘Sad Girls’ by Lang Leav. By using a qualitative descriptive analysis approach, this study explores the characteristics and factors that influence social avoidance behavior, as well as its impact on the main character's social avoidance. The data was collected from quotations, sentences, or character dialog in the novel SAD GIRLS which shows social avoidance in modern society. Then, the data was analyzed using social avoidant theory. The results of this study revealed that the characteristics of social avoidance include avoiding social encounters, minimizing conversations, and feeling uncomfortable in their social environment. In addition, two factors that influence a person to be socially avoidant are internal and external. Furthermore, there are several impacts of socially avoidant behavior, which include loneliness and isolation, difficulties in professional growth, and strained relationships.